Introducing unemployment insurance to developing countries - Milan Vodopivex (IZA Journal of Labor Policy, 2013)
The paper analyzes key labor market and institutional features of developing countries that affect functioning of unemployment insurance: a large informal sector, weak administrative capacity, and large political risk. It argues that these countries should tailor an OECD-style unemployment insurance program to their circumstances, among others by relying on self-insurance (via unemployment insurance savings accounts), complemented by solidarity funding, as a key source of financing; by simplifying monitoring of job-search behavior and labor market status; and by piggybacking on existing networks to administer benefits. The paper also addresses the question whether developing countries should introduce unemployment insurance.
Keywords: J65; J68; 330; unemployment; unemployment insurance; monitoring of benefits; unemployment insurance savings accounts; Arbeitslosenversicherung; Einführung; Institutionalismus; Moral Hazard; Ökonomischer Anreiz; Entwicklungsländer